1998
DOI: 10.1152/ajpheart.1998.274.1.h178
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and smooth muscle cell conduction in arterioles controlling blood flow

Abstract: We performed intracellular recording with Lucifer yellow dye microinjection to investigate the cellular pathway(s) by which constriction and dilation are conducted along the wall of arterioles (diameter 47 ± 1 μm, n = 63) supplying blood flow to the cheek pouch of anesthetized hamsters. At rest, membrane potential ( E m) of endothelial (−36 ± 1 mV) and smooth muscle (−35 ± 1 mV) cells was not different. Micropipette delivery of norepinephrine (NE) or phenylephrine (PE) produced smooth muscle cell depolarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
346
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(382 citation statements)
references
References 27 publications
33
346
3
Order By: Relevance
“…Local endothelial stimulation initiates a rapidly propagated, bidirectional wave of relaxation along the vessel axis (Welsh and Segal 1998;Figueroa et al 2003;de Wit et al 2006). An intact endothelium is required for conducted vasodilation, which does not decay with distance and so must contain a selfregenerative component.…”
Section: Gap Junctions In the Vascular Systemmentioning
confidence: 99%
“…Local endothelial stimulation initiates a rapidly propagated, bidirectional wave of relaxation along the vessel axis (Welsh and Segal 1998;Figueroa et al 2003;de Wit et al 2006). An intact endothelium is required for conducted vasodilation, which does not decay with distance and so must contain a selfregenerative component.…”
Section: Gap Junctions In the Vascular Systemmentioning
confidence: 99%
“…It has been reported that a T-type window current was responsible for a physiological, steady-state Ca 2 þ entry in human myoblasts (Bijlenga et al, 2000), and window currents in the V m range from À50 to À20 mV were suggested to account for high-K þ -induced, nifedipine-insensitive Ca 2 þ entry and vasoconstriction in rat mesenteric artery (Morita et al, 1999;Itonaga et al, 2002;Inoue & Mori, 2003). In pressurized small arterioles (hamster cheek pouch) resting V m measured in vivo was À35 mV (Welsh & Segal, 1998). Under physiological pressure, it is therefore likely that a window type Ca 2 þ current in mesenteric arterioles is either present or can be activated by small changes in V m .…”
Section: Biophysical Characteristics Of Non-l-type Channels In Mesentmentioning
confidence: 99%
“…Vasomotor signals spread along the vessel length through gap junctions connecting cells of the vessel wall, and thereby, participate in the minute-to-minute coordination of vascular resistance by integrating function of proximal and distal vascular segments in the microcirculation (de Wit et al, 2000;Figueroa et al, 2004Figueroa et al, , 2006. Although vasoconstrictor responses are thought to be conducted by smooth muscle cells (Welsh & Segal, 1998;Bartlett & Segal, 2000;Budel et al, 2003), the cellular pathway for conduction of vasodilator signals is more controversial and may be either exclusively by the endothelium (Emerson & Segal, 2000;Segal & Jacobs, 2001) or by both smooth muscle and endothelial cells (Bartlett & Segal, 2000;Budel et al, 2003). The cellular pathway for conduction of vasomotor responses has been studied by selectively damaging a short segment of endothelial cells or smooth muscle cells by injection of an air bubble via a side branch (Bartlett & Segal, 2000;Figueroa et al, 2007) or with a light-dye (fluorescein-conjugated dextran) treatment (Emerson & Segal, 2000).…”
Section: Conduction Of Vasomotor Responsesmentioning
confidence: 99%
“…In feed arteries, selective damage of the endothelium completely blocked the ACh-induced conducted vasodilation (Emerson & Segal, 2000;Segal & Jacobs, 2001), but in arterioles, either damage of the endothelium or the smooth muscle did not affect the ACh-induced conducted responses (Bartlett & Segal, 2000;Budel et al, 2003), which led to the proposal that the cellular pathway for conduction of vasodilations depends on the functional location of the vessel in the microvascular network (Segal, 2005). However, the cellular pathway of vasodilator signals may also depend on the stimulus that initiated the response, because, in contrast to ACh, selective damage of the endothelium blocked the vasodilation induced by bradykinin in arterioles (Welsh & Segal, 1998;Budel et al, 2003).…”
Section: Conduction Of Vasomotor Responsesmentioning
confidence: 99%
See 1 more Smart Citation